Negative effects of nicotine on bone-resorbing cytokines and bone histomorphometric parameters in male rats - Hapidin, Hermizi; Othman, Faizah; Soelaiman, Ima-Nirwana; Douglas A, Luke; Mohamed, Norazlina (https://doi.org/10.1007/s00774-006-0733-9, 2007)
The effects of nicotine administration on boneresorbing cytokines, cotinine, and bone histomorphometric parameters were studied in 21 Sprague–Dawley male rats. Rats aged 3 months and weighing 250–300 g were divided into three groups. Group 1 was the baseline control (BC), which was killed without treatment. The other two groups were the control group (C) and the nicotine-treated group (N). The N group was treated with nicotine 7 mg/kg body weight and the C group was treated with normal saline only. Treatment was given by intraperitoneal injection for 6 days/week for 4 months. The rats were injected intraperitoneally with calcein 20 mg/kg body weight at day 9 and day 2 before they were killed. ELISA test kits were used to measure the serum interleukin-1 (IL-1), interleukin-6 (IL-6), and cotinine (a metabolite of nicotine) levels at the beginning of the study and upon completion of the study. Histomorphometric analysis was done on the metaphyseal region of the trabecular bone of the left femur by using an image analyzer. Biochemical analysis revealed that nicotine treatment for 4 months signifi cantly increased the serum IL-1, IL-6, and cotinine levels as compared to pretreatment levels. In addition, the serum cotinine level was signifi cantly higher in the N group than in the C group after 4 months treatment. Histomorphometric analysis showed that nicotine signifi cantly decreased the trabecular bone volume (BV/TV), trabecular thickness (Tb.Th), double-labeled surface (dLS/BS), mineralizing surface (MS/BS), mineral appositional rate (MAR), and bone formation rate (BFR/BS), while causing an increase in the single-labeled surface (sLS/BS), osteoclast surface (Oc.S/BS), and eroded surface (ES/BS) as compared to the BC and C groups. In conclusion, treatment with nicotine 7 mg/kg for 4 months was detrimental to bone by causing an increase in the bone resorbing cytokines and cotinine levels. Nicotine also exerted negative effects on the dynamic trabecular histomorphometric parameters.